Training to Become a Mentor: Hungarian EFL Teachers’ Personal Discoveries - Pohl, Uwe; Révész, Judit (Working Papers in Language Pedagogy, 2014)
This article identifies and illustrates key developmental stages of a group of ELT mentor trainees during an intensive training course in Hungary. It reveals changes in the way the teachers defined their professional identities that amount to major steps in the participants’ development as teachers and mentors-in-training. As an account of how a highly structured teacher training event led to significant personal and professional development, the article also demonstrates the importance of the group process for participants to value and internalize the role of the mentor.